The Role of Opinion Leaders in the Acculturation of the Togutil Tribe in East Halmahera Regency, North Maluku Province - HASAN, Bahrudin; SIHABUDIN, Ahmad; JAMALULLAIL, Jamalullail (International Journal of Environmental, Sustainability, and Social Science, 2021)
One of the 21 tribal groups in North Maluku, the Togutil Tribe still closely upholds its traditional beliefs and practices. They also form their own community and restrict interaction and communication with other ethnic groups, such as the Maba tribe. This study aimed to determine how opinion leaders' role in the acculturation between the Togutil tribe and the Maba tribe caused acculturation in East Halmahera Regency. The research approach used is qualitative research, which seeks to understand, explain and analyze the acculturation process between the Togutil tribe and other ethnic communities in the "Gam Rangge" customary area of East Halmahera Regency. The results showed that the communication process between the Togutil tribe and religious leaders, traditional leaders, community leaders and the government had been going on for a long time since 1984 and had a direct impact on cultural acculturation. The existence of religious leaders and community leaders has an essential role in providing awareness to the Tugutil people in the forest interior of East Halmahera Regency to acculturate with the local community.